LAYOUT ANALYSIS OF EQUIPMENT STORAGE AREA TO CREATE SAFE FLOW IN AIRPORT - Muhammad Ridho Windriansyach; Minulya Eska Nugraha; Fitri Masitoh; Shabrina Ramadhani; Zusnita Hermala (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2023)
The flow access road in the airport make-up area still has obstacles from many Grounds Support Equipment (GSE) scattered during operational and non-operational hours that can be a hazard endangering ground handling officers and passengers. This study aims to overview the problems in the make-up area of Jenderal Ahmad Yani Semarang International Airport and provide a solution with a new layout of GSE to make a safe flow in the make-up area. This research used descriptive qualitative methods, data collection by observation, interview, and documentation with analytics design by Miles and Huberman. The solution to the problem in this study is designing a new eastern equipment parking area layout by optimizing the empty land of former containers and providing land for Baggage Carts (BCT) to make it tidier. The conclusion of this study is a layout design of the equipment storage area that can optimize the empty land of the former container into additional land to make equipment area storage more efficient and safe. The researcher also provides land for baggage carts. Hence, their placement is neater to avoid becoming an obstacle and suggests that third parties consider this research, which can also be applied at Jenderal Ahmad Yani Semarang International Airport.